Severity, uncertainty, social support and coping style of parents who have children with epilepsy: a structural equation model - Miao Zhang; Liyun Lei; Dan Yao; Yongai Zhang (Frontiers in Neurology, 2025)
AimTo examine four variables in the model of perceived uncertainty in illness in northwestern China; to explore the relationship between severity, social support, illness uncertainty, and active coping in parents of children with epilepsy.DesignA cross-sectional study design.Reporting methodThe STROBE checklist was used to ensure the rigor in this study.MethodThis study recruits parents of children with epilepsy from a tertiary children’s hospital using convenience sampling between January and November 2024. Eligible participants completed questionnaires via an online platform (https://www.wjx.cn/) by scanning the QR code. Structural equation modeling and mediated effects serve as the methods for data analysis.ResultThis study surveyed 492 parents, including 192 males (39.0%) and 300 females (61.0%). The corrected model achieved an acceptable model fit: (χ2 = 89.104 (p < 0.001); df = 59; χ2/df = 1.510; RMSEA = 0.043; CFI = 0.960; TLI = 0.941; IFI = 0.969). Severity positively predicted illness uncertainty (β = 0.105, p < 0.05). Social support negatively predicted illness uncertainty (β = −0.111, p < 0.05) and positively predicted active coping (β = 0.583, p < 0.001). Illness uncertainty negatively predicted active coping (β = −0.075, p < 0.05). Social support had a direct positive effect on active coping (β = 0.550, p < 0.01), and social support had an indirect negative effect on active coping through uncertainty (β = −0.012, p < 0.001).ConclusionIllness uncertainty partially mediated the relationship between social support and active coping. However, we did not confirm a relationship between illness severity and active coping in this study.